Ladybug at Orchard Avenue = Mariquita en la Avenida Orchard - Zoehfeld, Kathleen Weidner; Buchs, Thomas (Norwalk, Conn. : Soundprints, 2008)
Ladybug rambles through the garden, up and down rose stems in search of her favorite food, aphids, instinctively using her natural defenses to escape from threats.
Keywords: Ladybugs -- Fiction; Bilingual books -- English-Spanish